Uji antibakteri gel hand sanitizer ekstrak daun bawang (Allium fistulosum) tehadap bakteri Staphylococcus aureus - Nurasni Nurasni; Elfia Neswita (Journal of Pharmaceutical and Sciences, 2023)
The ability to inhibit bacterial growth from hand sanitizer gel is quite good. Leeks (Allium fistulosum) contain allicin which can function as an inhibitor of the growth of Staphylococcus aureus bacteria. This research aimed to eamine the antibacterial activity of Staphylococcus aureus from Hand Sanitizer gel containing leek extract. The procedure includes making simplicia, characterization, and making extracts through maceration with concentrations of 20%, 30%, and 40%, then carrying out an antibacterial test using the agar diffusion method. The test results showed that the bacterial inhibition zone at concentrations of 20%, 30%, and 40% respectively was 3.5 mm; 5.0mm; and 5.9 mm in the medium category. This research concludes that the formulation with the best concentration is the formulation with a concentration of leek extract as large as the inhibition zone for Staphylococcus aureus bacteria in the medium category.